The influence of homosexual images in Chinese online advertising on the attitudes of young Chinese consumers: A study based on undergraduate students in Chinese universities - WANG, JIAYI (2022)
The growing social support for the gay community, combined with this group's potentially great purchasing power, has sparked increased interest in the gay market among marketers. In order to more effectively target both this group and the general market, some brands have created advertising featuring homosexual people for the Chinese market in recent years. This study aims to investigate how homosexual advertising on the Chinese Internet influences young consumers' attitudes towards advertising and brands, with influencing factors including gender, sexual orientation, place of residence, Internet use and beliefs in Confucianism. The results of the study show that young Chinese consumers who are female, LGB, live in first-tier cities and use the internet regularly have more positive attitudes toward homosexual advertising. The study revealed that there was no significant association between consumers' beliefs in Confucianism and their attitudes towards homosexual advertising. Furthermore, the results show that there is a significant positive correlation between attitudes towards brands and attitudes towards homosexual advertising. The more positive consumers' attitudes towards homosexual advertising, the more favourable their attitudes towards the brand. Finally, management implications and recommendations for future research are discussed.